Numerical inversion techniques in the recovery of molecular weight distribution expressed in different transformed domains: experimental validation - Brandolin, Adriana (2001)
In this work we analyze the feasibility of using numerical inversion techniques for recovering MWD of actual polymers from a transformed domain, specifically the one defined by probability generating functions. We start from known experimental MWDs, transform them, and then apply two different numerical techniques to recover the MWD. We analyze the influence of noise in the calculated probability generating functions on the quality of the recovered molecular weight distributions. We also study how the range of molecular weight selected for the inversion procedure affects the results. We compare the recovered distributions obtained by both methods and suggest a criterion for establishing the reliability of a given solution. We find that this general strategy is appropriate for the recovery of MWDs whether they are monomodal, multimodal, wide or narrow. This provides a tool for the treatment of actual polymerization systems for which there is no analytical solution for the mass balance equations.